An Assessment Of Seaport Privatization In Saudi Arabia : A Case Study Utilizing Grounded Theory Approach - Al-Yagout, areed Mohammed (2011)
Saudi Arabia, one of the late adopters of the privatization as compared to other countries, has embarked on the privatization policy in late 1990s with seaports being one of the earliest sectors that the government opened up for private sector involvement. The purpose of this research is to study the seaports privatization outcome after nearly 10 years of its implementation and to evaluate whether the declared privatization objectives have been achieved and the contributory positive / negative factors, as well as to suggest curative measures to mitigate the shortcomings, if any.